Eksistensi Lingkungan Belajar Fil Qur’an Wal Hadits - Pepen Supendi Setiawan; Yayat Suharyat (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
The environment is a place where there is a unity between space and all objects, energy, resources and conditions as well as living things including humans, animals, plants and their behavior that influences nature itself. The learning environment in the Qur'an is not clearly stated, but the learning environment can be related to places where education takes place, such as mosques, homes, madrasas, and others. We must be able to understand the learning environment itself because the Qur'an only gives hints about the learning environment, namely the family, community and madrasah. In other words, the learning environment is a place where we can interact to gain useful knowledge, not necessarily looking at the place where we get the knowledge, but how we practice it and apply it in everyday life.